Numerical simulation of boundary heat flow effects on directional solidification microstructure of a binary alloy - Xue Xiang (China Foundry, 2010)
The boundary heat flow has important significance for the microstructures of directional solidified binary alloy. Interface evolution of the directional solidified microstructure with different boundary heat flow was discussed. In this study, only one interface was allowed to have heat flow, and Neumann boundary conditions were imposed at the other three interfaces. From the calculated results, it was found that different boundary heat flows will result in different microstructures. When the boundary heat flow equals to 20 W·cm-2, the growth of longitudinal side branches is accelerated and the growth of transverse side branches is restrained, and meanwhile, there is dendritic remelting in the calculation domain. When the boundary heat flow equals to 40 W·cm-2, the growths of the transverse and longitudinal side branches compete with each other, and when the boundary heat flow equals to 100-200 W·cm-2, the growth of transverse side branches dominates absolutely. The temperature field of dendritic growth was analyzed and the relation between boundary heat flow and temperature field was also investigated.